2017
DOI: 10.1123/jis.2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Ticket Pricing in the Collegiate Environment: An Agenda for Research

Abstract: As pressure mounts for intercollegiate athletic departments to be more selfsufficient, administrators must respond by increasing generated revenues. Despite the importance of ticket sales in this endeavor, however, little is known about the underlying ticket pricing structures and policies used by National Collegiate Athletic Association (NCAA) institutions. Of the limited existing scholarship focused on managerial pricing decisions in the field of sport management, only professional sports settings have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Sport science encompasses the scientific inquiry into the overall phenomena of sport (18,22,23,31). As such, sport science is a multidisciplinary field generally concerned with improving outcomes in sport (4,23), including but not limited to identifying and developing talent (28), mitigating injury risk (9), enhancing physical fitness (38), increasing ticket sales (39), improving fan experience (32), and, ultimately, winning (24).…”
Section: Envisioning a Sport Science Departmentmentioning
confidence: 99%
“…Sport science encompasses the scientific inquiry into the overall phenomena of sport (18,22,23,31). As such, sport science is a multidisciplinary field generally concerned with improving outcomes in sport (4,23), including but not limited to identifying and developing talent (28), mitigating injury risk (9), enhancing physical fitness (38), increasing ticket sales (39), improving fan experience (32), and, ultimately, winning (24).…”
Section: Envisioning a Sport Science Departmentmentioning
confidence: 99%
“…Such a study might provide additional evidence to determine whether mimetic isomorphic behavior is indeed driving decision making (Lipsey et al, 2021). In fact, a prior study by Morehead et al (2021) suggested college athletics administrators are guided by several competing motives when setting ticket prices, with profit maximization serving as just one of many strategies. A similar finding could emerge among development personnel; perhaps a department's short-term goal is to generate the maximum number of donors initially, with an objective of cultivating those donors in to higher-end donors in ensuing years.…”
Section: Limitations and Future Researchmentioning
confidence: 99%